THE CORRELATION BETWEEN STRESSOR AND WORK ACHIEVEMENT THROUGH WORK STRESS ON THE EMPLOYEES IN THE MARKETING DIVISION OF SINAR JAYA MULTIPURPOSE COOPERATIVE MALANG - Wibowo, Heri (Department of Management, 2014)
This study aimed at investigating the correlation between stressor and work stress, stressor and work achiavement, work stress and work achievement, and stressor and work achievement through work stress on the employees in the marketing division of Sinar Jaya cooperative, Malang. This descriptive-quantitative study employed mathemathical methods in describing the phenomena, while scale analysis method was used to describe the levels of the employees? stressor, work stress, and work achiavement. Inaddition, the path analysis was used in testing the coutribution that was indicated by the path coefficient between the employees? stressor, work stress, and work achievement variables. The average result of the scale analysis revealed that the stressor, work stress, and work achievement variables were considered high. Furthermore, the result of the path analysis also showed a significant correlation between stressor and work achievement through work stress. Keyword : Marketing Employees, Stressor, Work Stress, Work Achivement